RANCANG BANGUN ALAT FIKSASI SEKALIGUS CASSETTE HOLDER UNTUK PEMERIKSAAN RADIOGRAFI ABDOMEN PROYEKSI LLD (LEFT LATERAL DECUBITUS) PADA PASIEN NON KOOPERATIF - Agustina Dwi Prastanti; Kevin Ade Juliantino; Ardi Soesilo Wibowo; Siti Daryati (Poltekkes Kemenkes Semarang, 2020)
Background: Research on the design of fixation devices as well as cassette holders for projection of abdominal radiography in LLD (left lateral decubitus) in non-cooperative patients is motivated by difficulties in fixing patients and placing tapes by radiographers during LLD (left lateral decubitus) radiographs with non-patient conditions cooperative. The purpose of making a design is to replace the patient's family role in holding patients and tapes during the examination.Methods: This type of research is applied research. The method used in data collection is designing tools, using tools, testing the performance of tools, testing the function of tools. The performance test and the function test of the tool were carried out directly on the patients at the RSK Radiology Installation Ngesti Waluyo Parakan. The results of the performance test and function test were analyzed based on the check list of respondents regarding the work value of the tool.Results: The design of this fixation tool consists of a supporting iron component, patient stand, cassette holder, strap strap. The performance test of the tool is in accordance with the specifications of the tool made by the author. Function tests are divided into two, namely function tests based on the technique of using tools and based on the radiograph produced. Function tests based on the use of tools techniques obtained a total work value of 3.1 can be concluded the function of a tool based on the technique of good use.Conclusions: Function tests based on the resulting radiographs obtained a total work value of 3.33 can be concluded that the function of a tool based on the resulting radiograph is good